Activity of solid catalysts for biodiesel production: A review - Zabeti, M.; Daud, W.M.A.W.; Aroua, M.K. (Fuel Processing Technology, 2009)
Heterogeneous catalysts are promising for the transesterification reaction of vegetable oils to produce biodiesel. Unlike homogeneous, heterogeneous catalysts are environmentally benign and could be operated in continuous processes. Moreover they can be reused and regenerated. However a high molar ratio of alcohol to oil, large amount of catalyst and high temperature and pressure are required when utilizing heterogeneous catalyst to produce biodiesel. In this paper, the catalytic activity of several solid base and acid catalysts, particularly metal oxides and supported metal oxides, was reviewed. Solid acid catalysts were able to do transesterification and esterification reactions simultaneously and convert oils with high amount of FFA (Free Fatty Acids). However, the reaction rate in the presence of solid base catalysts was faster. The catalyst efficiency depended on several factors such as specific surface area, pore size, pore volume and active site concentration.